Bioaccumulation and metal-associated biomarker responses in a freshwater mussel, Dreissena polymorpha, following short-term platinum exposure. (March 2019) - Brand, Sarel J.; Erasmus, Johannes H.; Labuschagne, Marelize; Grabner, Daniel; Nachev, Milen; Zimmermann, Sonja; Wepener, Victor; Smit, Nico; Sures, Bernd
Abstract: Due to the increasing presence of platinum (Pt) in the environment, the caveat arises to identify its toxic potential in species at risk of being exposed – especially those found in aquatic environments where pollutants tend to accumulate. Comprehensive characterisation of possible adverse effects following exposure of aquatic organisms to Pt remains elusive. To address this, Zebra mussels ( Dreissena polymorpha ) were exposed to a range of Pt(IV) concentrations (0.1, 1, 10, 100 and 1000 μg/L) for one and four days, respectively, after which bioaccumulation was quantified and compared to alterations in biomarker profiles relevant to metal toxicity i.e. glutathione-S-transferase (GST) and catalase (CAT) activity, lipid peroxidation and metallothionein (MT) induction. Despite pre-conditioning of the tanks, Pt recovery in the exposure media was found to be 36% (0.1 μg/L), 42% (1 μg/L), 47% (10 μg/L), 68% (100 μg/L) and 111% (1000 μg/L) due to biological and non-biological processes. Pt concentrations in dried mussel soft tissue increased with exposure concentrations and were 20–153 times higher compared to quantified Pt concentrations in the exposure media. CAT activity was significantly increased in the tissue of mussels exposed to 0.1–100 μg/L Pt after Day 1 while the lowest effect concentration (LOC) for this response on both Day 1 and Day 4 was 0.1 μg/L. The effect on the GST activity was less pronounced but demonstrated a similar trend. However, enhanced lipid peroxidation was measured in the tissue of mussels exposed to ≥0.1 μg/L on Day 4. Bioaccumulation of Pt was also associated with a concentration-dependent increase in Pt-MT. Although these effects occurred at Pt levels higher than those present in the environment, it indicates that Pt has the ability to cause aberrancies in metal-associated biomarker profiles. Graphical abstract: Image 1 Highlights: Pt accumulation in Zebra mussel soft tissue increased with exposure concentration. Pt exposure induced antioxidant enzyme systems (CAT and GST). Lowest effect concentration for catalase was 0.1 μg Pt/L. Pt exposure increased lipid peroxidation (MDA conjugates). Metallothionein increased with Pt tissue levels. Abstract : During the current study, Pt was found to bioaccumulate in mussel soft tissue. This led to an increased presence of lipid peroxidation, the induction of antioxidant enzyme systems and binding of Pt to metallothioneins proportionate to exposure concentration.